The SIR model simulation: the effectiveness of Covid-19 vaccination strategies in Malaysia / Muhammad Fathillah Che Hassan and Muhammad Aidil Adzha Che Anuar - Che Hassan, Muhammad Fathillah; Che Anuar, Muhammad Aidil Adzha (2022)
Covid-19 is a new coronavirus disease that was labeled a pandemic by the World Health Organization (WHO) in March 2020. SIR Model is a versatile compartmental mathematical tool that may be used to simulate any pandemic dynamic, including the current Covid-19 outbreak. In the conventional SIR model, the total population (N) is divided into three categories: susceptible(S), infected(I), and recovered(R). So, this research focused on finding the basic reproductive number, Ro of Covid-19 by using the Next Generation Matrix. Ro is greater than 1 means viruses begin to spread the population and Ro less than 1 means disease is about to vanish from the population. It is also analyze and compare the transmission of Covid-19 with and without vaccination. To apply this, the data from government websites is used to find the total number of cases and recover. With the help of mathematical software such as Maple to find the result of the graph. From the result produce from Maple, it can be observed that the slope of with vaccination is bigger than the slope of without vaccination. It clearly shows the comparison between them. The findings improved by having vaccination and then transmission rate low is good to decrease virus Covid-19 from infection.